LAJU KEMUNDURAN MUTU IKAN LELE (Clarias sp.) PADA PENYIMPANAN SUHU CHILLING - Anhar Rozi (Universitas Teuku Umar, 2018)
Catfish (Clarias sp.) is one type of freshwater fish. Quality of deterioration of fish takes place in a very fast, so it takes the right treatment to inhibit decay processes that occur either chemically or enzymatically. The aimed of this studywas performed to determine the rate of quality deterioration of catfish phase pre rigor, rigor mortis, and post rigor during storage chilling temperature. The proximate value of catfish content for protein, moisture, ash,fat, and carbohydrate was 2.94%, 77.78%, 1.35%, 0.95%, 16.96% respectevely. Results of pH testedincrease from 6.61to be 6.81. TVB values of catfish had varies between from 14.18 to 739.2 mg N/100g, whereas TPC value from 0.95 x105to 55x105 colonies/g.Storage of catfish with chilling temperature was can inhibit quality of deterioration, becasuse the lower remperature inhibit activities for microbiological, biochemical and enzymatic.